Essentials of marketing a marketing strategy planning approach - Perreault, William D.; Cannon, Joseph P.; McCarthy, E. Jerome (Edmund) (McGraw-Hill Education, 2021)
"This book is about marketing and marketing strategy planning. At its essence, marketing strategy planning is about figuring out how to do a superior job of satisfying customers. This edition we focused on (1) marketing analytics, (2) currency, and (3) active learning"-- Provided by publisher.